CRIMINALIZATION 'A POLICY' “JURIDICAL REVIEW BASED ON GOOD GOVERNANCE ASPECTS” - Situmeang, Tomson; Sectionardo, William Andrew; Berutu, Chris Anggi Natalia (Veredas do Direito, 2025)
Public policy serves as a vital instrument through which the government regulates society, addresses public needs, and promotes welfare. However, the increasing complexity of governance sometimes results in policies that inadvertently cause state losses, particularly financial ones. This raises critical legal debates on whether such policy outcomes should lead to criminal prosecution. In Indonesia, this issue has become more prominent with cases involving public officials criminalized for policy failures made in good faith. This study employs a normative juridical approach, examining statutory frameworks and legal doctrines governing public administration and anti-corruption law. It focuses on Law No. 30 of 2014 on Government Administration and Law No. 31 of 1999 as amended by Law No. 20 of 2001 on the Eradication of Corruption. Central to the analysis are the concepts of freies Ermessen (administrative discretion) and the General Principles of Good Governance (AAUPB). Findings reveal that policy decisions should not be criminalized solely due to unfavorable outcomes. Criminal liability arises only when policies are made with malicious intent or violate governance principles. The study calls for clearer legal standards to protect lawful discretion while maintaining accountability and promoting legal certainty in governance.